The political structures and its influences in sport development in the state of Paraná, Brazil: the case of athletics - Lenamar Fiorese Vieira; José Luiz Lopes Vieira (Journal of Physical Education (Maringá), 2008)
This study aimed to investigate political structures and its influence over sport talents development in athletics, in the state of Paraná, having as basis the BRONFENBRENNER (1979, 1992, 1995) ecological systems theory. The model for this study was the person- process- context – time biological paradigm. Informer's record, semi-structured interview, research diary and documents, were used to collect the data. The sample comprised athletics talented individuals (14), their relatives (13), coaches (7) directors from Paraná Esporte (3) and a State Secretary for Sports of Paraná. Category contents analysis through outlines, enumeration and categories were used to analyze the data. The results showed that two historical periods happened at state government level: from 1983 to 1990, with the development of programs and projects that instigated athletics talent development in the state of Paraná; from 1991 to 1998 such policy had no continuity, which depreciated athletics in the state. The state governments structure dynamics at the different periods interfered significantly in the Paraná's athletics talents development. Therefore, the personal trajectory of each of these talented individuals is characterized by a unique process, closely related to many years of training process, being dependent of administrative structures.